2002
DOI: 10.1128/aem.68.6.2917-2923.2002
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus bulgaricus Proteinase Expressed in Lactococcus lactis Is a Powerful Carrier for Cell Wall-Associated and Secreted Bovine β-Lactoglobulin Fusion Proteins

Abstract: Lactic acid bacteria have a good potential as agents for the delivery of heterologous proteins to the gastrointestinal mucosa and thus for the reequilibration of inappropriate immune responses to food antigens. Bovine ␤-lactoglobulin (BLG) is considered a major allergen in cow's milk allergy. We have designed recombinant Lactococcus lactis expressing either full-length BLG or BLG-derived octapeptide T6 (IDALNENK) as fusions with Lactobacillus bulgaricus extracellular proteinase (PrtB). In addition to construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…lactis was already used to produce entire Blg protein, and recombinant strains were shown to be immunogenic after intranasal and oral administration in mice (7). More recently, Bernasconi et al (5) showed that the Lactobacillus bulgaricus exported protease PrtB could enhance the export of both entire Blg and a poorly antigenic Blg peptide in L. lactis. Here, we constructed an L. lactis strain producing Blg41-60::Nuc, a recombinant fusion protein between Blg41-60 and the mature part of the staphylococcal nuclease (Nuc) (26), by use of the nisin-inducible expression system (9).…”
mentioning
confidence: 99%
“…lactis was already used to produce entire Blg protein, and recombinant strains were shown to be immunogenic after intranasal and oral administration in mice (7). More recently, Bernasconi et al (5) showed that the Lactobacillus bulgaricus exported protease PrtB could enhance the export of both entire Blg and a poorly antigenic Blg peptide in L. lactis. Here, we constructed an L. lactis strain producing Blg41-60::Nuc, a recombinant fusion protein between Blg41-60 and the mature part of the staphylococcal nuclease (Nuc) (26), by use of the nisin-inducible expression system (9).…”
mentioning
confidence: 99%
“…Proteins of interest were already genetically inserted in the catalytic domain of the proteinase PrtB. This system was successfully used for the expression of different antigens, such as beta-lactoglobulin and immunoglobulin E mimotopes, as tools for the modulation of tolerance and allergy (1,32). …”
Section: Discussionmentioning
confidence: 99%
“…A fragment comprising amino acids 280 to 467 of L. bulgaricus mature cell wall proteinase was overexpressed in Escherichia coli and used for production of antiserum in rabbits (1).…”
Section: Methodsmentioning
confidence: 99%
“…Appropriate combinations of promoter, signal sequence and anchoring signal sequences under suitably efficient promoters are required for satisfactory surface expression in the lactic acid bacteria (Bernasconi et al. 2002).…”
Section: Introductionmentioning
confidence: 99%